Combined effects of polyethylene spiked with the antimicrobial triclosan on the swamp ghost crab (Ucides cordatus; Linnaeus, 1763) - Nobre, Caio Rodrigues [UNESP]; Moreno, Beatriz Barbosa; Alves, Aline Vecchio; de Lima Rosa, Jonas; Fontes, Mayana Karoline [UNESP]; Campos, Bruno Galvão de [UNESP]; Silva, Leticia Fernanda da [UNESP]; Almeida Duarte, Luís Felipe de; Abessa, Denis Moledo de Souza [UNESP]; Choueri, Rodrigo Brasil; Gusso-Choueri, Paloma Kachel; Pereira, Camilo Dias Seabra (Elsevier, 2022)
Domestic sewage is an important source of pollutants in aquatic ecosystems and includes both microplastics (MPs) and pharmaceuticals and personal care products (PPCPs). This study sought to assess the biological effects of the interaction between plastic particles and the antibacterial agent triclosan (TCS). The study relied on the swamp ghost crab Ucides cordatus as a model. Herein polyethylene particles were contaminated with triclosan solution. Triclosan concentrations in the particles were then chemically analyzed. Swamp ghost crab specimens were exposed to experimental compounds (a control, microplastics, and microplastics with triclosan) for 7 days. Samplings were performed on days 3 (T3) and 7 (T7). Gill, hepatopancreas, muscle and hemolymph tissue samples were collected from the animals to evaluate the biomarkers ethoxyresorufin O-deethylase (EROD), dibenzylfluorescein dealkylase (DBF), glutathione S-transferase (GST), glutathione peroxidase (GPx), reduced glutathione (GSH), lipid peroxidation (LPO), DNA strands break (DNA damage), cholinesterase (ChE) through protein levels and neutral red retention time (NRRT). Water, organism, and microplastic samples were collected at the end of the assay for post-exposure chemical analyses. Triclosan was detected in the water and crab tissue samples, results which indicate that microplastics serve as triclosan carriers. Effects on the gills of organisms exposed to triclosan-spiked microplastics were observed as altered biomarker results (EROD, GST, GPx, GSH, LPO, DNA damage and NRRT). The effects were more closely associated with microplastic contaminated with triclosan exposure than with microplastic exposure, since animals exposed only to microplastics did not experience significant effects. Our results show that microplastics may be important carriers of substances of emerging interest in marine environments in that they contaminate environmental matrices and have adverse effects on organisms exposed to these stressors.
Keywords: Adsorption; Emerging pollutants; Microplastics; Plastic waste; Toxicity